2018
DOI: 10.1136/jmedgenet-2017-104863
|View full text |Cite
|
Sign up to set email alerts
|

Agalsidase alfa versus agalsidase beta for the treatment of Fabry disease: an international cohort study

Abstract: BackgroundTwo recombinant enzymes (agalsidase alfa 0.2 mg/kg/every other week and agalsidase beta 1.0 mg/kg/every other week) have been registered for the treatment of Fabry disease (FD), at equal high costs. An independent international initiative compared clinical and biochemical outcomes of the two enzymes.MethodsIn this multicentre retrospective cohort study, clinical event rate, left ventricular mass index (LVMI), estimated glomerular filtration rate (eGFR), antibody formation and globotriaosylsphingosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 41 publications
(45 reference statements)
7
71
0
6
Order By: Relevance
“…Both agalsidase-a and agalsidase-b have been demonstrated to benefit patients in the short term and, in observational studies, patients treated for up to 10 years showed stabilization of eGFR or a slowing of the progression of eGFR decline. 19,20,[28][29][30][31][32][33][34][35][36] The natural course of disease is associated with a rapid decline of renal function (eGFR decline up 12 ml/min per 1.83 m 2 per year) and left ventricular hypertrophy. 37 Tables 1 to 5 provide a general overview of the effects of both ERTs on symptoms and manifestations in patients with FD.…”
Section: Fd-specific Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Both agalsidase-a and agalsidase-b have been demonstrated to benefit patients in the short term and, in observational studies, patients treated for up to 10 years showed stabilization of eGFR or a slowing of the progression of eGFR decline. 19,20,[28][29][30][31][32][33][34][35][36] The natural course of disease is associated with a rapid decline of renal function (eGFR decline up 12 ml/min per 1.83 m 2 per year) and left ventricular hypertrophy. 37 Tables 1 to 5 provide a general overview of the effects of both ERTs on symptoms and manifestations in patients with FD.…”
Section: Fd-specific Treatmentmentioning
confidence: 99%
“…[38][39][40][41] Furthermore, ERT has been reported to stabilize renal function in terms of eGFR, whereas ERT's effect on proteinuria and albuminuria is inconsistent. 26,[29][30][31][32][33][34][35][36][37][42][43][44][45][46][47][48][49][50][51][52] If ERT is started before myocardial fibrosis has developed, a long-term improvement of myocardial morphology, function, and exercise capacity can be achieved. [53][54][55][56][57][58][59][60][61][62] It also leads to a reduction of cerebrovascular and thromboembolic events [63][64][65] and significant improvement in pain-related quality of life.…”
Section: Fd-specific Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a greater biochemical response and an improved ventricular mass was observed with agalsidase β(51). An improved estimated glomerular filtration rate (eGFR) is also associated with the use of agalsidase β after switching drug from agalsidase α formulation (52) A recent Cochrane report confirmed that agalsidase β may be associated to a lower incidence of cerebrovascular events than agalsidase α(53).…”
Section: Introductionmentioning
confidence: 99%
“…4), it was also demonstrated that the formation of neutralising anti-drug antibodies (ADA) reduce therapy efficiency, mainly in male patients (up to 70% of treated males). [5][6][7][8][9][10][11][12][13] Interestingly, ADAs demonstrate a high cross-reactivity for both recombinant enzymes (Linhorst et al 2004). 7 There is evidence that the risk for the formation of ADAs is mainly determined by the presence of endogenous enzyme 6,7 and the dose of infused recombinant enzyme.…”
mentioning
confidence: 99%